Let's Take 5 Cafe - Romainor, Najibulla; Riman, Izzaidah; Amat, Mohd Azif; Mohd Awang, Mohammad Imran; Marimuthu, Shareenie Mariely Ayu (2012)
"Let's Take 5 Cafe" is an official name for our company as it symbolises "take a break". It is a business involve in Food and Beverage Industry in Malaysia. We are different than other cafes in UiTM because we focus mainly on coffee. Our coffee differs in types and taste, as well as the ways to prepare them. Our cafe would promise the most pleasant services and make sure that the customers enjoy our beverages fully. The location of our cafe would be inside the educational institute known as UITM Sepanggar, Sabah branch. We believe the location we have chosen to set up our cafe is very strategic to attract the students in UiTM for they are the targeted market. We provide the customers with the decision of taking ur beverages on the spot or on the go. We provide take away with special cups, to withstand the hot beverages and it is also environmentally friendly because of it biodegradable characteristics.